PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KONSUMEN TAYANGAN VIDEO DI YOUTUBE DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Asih Artina; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Youtube is a video-sharing wen (sharing video) site where users can load,watch and share video clips for free. Generally the videos on youtube are musicclips (video clips), movies, TV, and videos made by its own users. But in realitythere are many videos of adult songs displaying inappropriate impressions seenby immature or incompetent children because the video contains verbalpornographic elements through titles and / or lyrics that are sexually charged orobsceneAs for the purpose of writing this thesis is to know the legal protection andobligations of the old orag to the child as a consumer of video clips of adult songson youtube viewed from the law number 8 of 1999 on consumer protection. Inwriting this thesis, the authors use the type of research that is legal literatureresearch.The conclusions can be obtained from this study is First, the legalprotection of children as consumers of video clips of adult songs on youtube isstill not running properly, where there are still many children as consumers whoare harmed due to video clips of adult songs on youtube that mostly contain thingsnegative things such as the element of pornography, not educational, chargedscenes and / or lyrics that can be seen to make women as the object of sex, theform of violence. Secondly, the obligations and responsibilities of parents andgovernment to children as adult video clip users on youtube are parents need tohave knowledge about the internet (youtube), restrict the use of internet tochildren, build and equip children with religious education in the family as earlyas possible. The writer's suggestion in writing this thesis is First, it is expectedthat the consumer of video clip of adult song on youtube can be more donepenyarigan about age restriction that can watch the show, and also video clip ofadult song not to highlight things that smell of pornography, and other tangiblethings. Second, it is expected that parents can better control every child's actions,directing the child to positive things. For the government is expected toimmediately provide a best solution in overcoming the negative impact of theinternet that will affect the child's development in particular.Keywords: Legal Protection - Child - Consumer - Video Clip - Adult Song -Youtube